How Do Spanning External Fixators on Knee Dislocation Patients Affect the Use of MRI and Knee Stability? - Javidan, Pooya; Owen, Joshua; Cutuk, Adnan; Watson, Tracy; Kaar, Scott (The Journal of Knee Surgery, 2015)
This study sought to determine the following: (1) Does the external fixator compromise quality of imaging obtained? (2) How do findings from the evaluation under anesthesia at the time of external fixator removal compare with the initial magnetic resonance imaging (MRI) findings? This was a retrospective study of a consecutive patient series at an academic level 1 trauma center. There were 19 consecutive patients with traumatic knee dislocations and spanning external fixator applied. Each patient had a knee MRI with the external fixator in place and examination at the time of external fixator removal. A review of knee stability at the time of external fixator removal with physical examination and stress fluoroscopy were performed. Our study revealed only minor incidence of poorly visualized structures. Clinical stability was present after fixator removal in only 11 of 14 medial collateral ligament tears, 4 of 16 lateral collateral ligament tears, 1 of 19 anterior cruciate ligament tears and 3 of 19 posterior cruciate ligament tears. MRI is a useful imaging modality in the setting of knee dislocations placed in spanning external fixators. Patients' knees largely remain unstable after external fixator removal.
Keywords: knee dislocation; magnetic resonance imaging; external fixator